Issues and concern of wives who were infected with HIV and lost their husbands to AIDS in Malaysia - Md. Zain, Rajwani; Baba, Ismail (2009)
The impact of HIV/AIDS on women has not been fully understood and researched. As a result of that many women are suffering in silent especially to those who do not have access to health and social services. A research on issues and concern of wives who have been infected with HIV and lost their husbands to AIDS was conducted in 2008 in the northern part of Malaysia. The main objective of the study was to explore what are some of the impacts of HIV/AIDS on women in Malaysia. A qualitative research was used as a method of the study. An in-depth interviewed were made to seven women who were infected with HIV from their husbands.A purposive sampling was used and most of these women were living in villages of the north part of West Malaysia. Four main themes were identified in the study; they were stigma and discrimination, coping strategies, bereavement and care giving. Results showed that many of these women are still suffering from stigma and discrimination. These women felt that people were still afraid to associate with them. Many became withdrawn and feeling helpless with their HIV status. Fear of others knowing about their HIV continues and there was nobody to turn to for psychosocial help. Many have suffered in silent. Care giving also became a problem after their husbands died of AIDS. Many were not able to get jobs because they had never worked before even when their husbands were still alive. Therefore, care giving has become an issue to these women. In conclusion, the findings suggest that actions need to be taken in order to help these women cope better with their HIV status.Government and non-government agencies should continue their activities to reduce stigma and discrimination especially in the northern region of Malaysia especially when the numbers of women who have been infected with HIV continue to rise. Access to health and social services should be strengthening if we were to help these women.